PENGARUH APLIKASI DISCORD DALAM PEMBELAJARAN DARING TERHADAP HASIL BELAJAR PADA MATAKULIAH KOMPUTER - Ridho, M.Rasyid; Muhaimin, Muhaimin; Harjono, Harry Soedarto (Jurnal Ilmiah Bina Edukasi, 2021)
This study aims to explain the influence of Discord application in online learning on student learning outcomes and motivation. Quantitative method with quasi-experimental design with 40 samples. Data collection uses tests and questionnaires, analysis data using instrument tests, normality, homogeneity, while hypothetical tests use Wilcoxon, Mann-Whiteney (U), and Spearman tests. The results of post-test experiment class obtained an average score 83.5 higher than control class 61.25. Based on Wilcoxon Test Asymp.Sig (2-tailed) obtained 0.000 < 0.05, Ha1 received, Mann-Whiteney Test (U) High motivation obtained U= 1,500 Asymp.Sig (2-tailed) obtained 0.000 < 0.05, Ha2 Low motivation obtained U=0.000 Asymp.Sig (2-tailed) obtained 0.000 < 0.05, Ha3 received, there is a significant difference between the results of using discord application and using Whatsapp, Spearman Test Asymp.Sig (2-tailed) obtained 0.000 < 0.05, Ha4 received, correlation coefficient value of 0.973** means the relationship between learning motivation variables and learning outcomes is very strong.